2010
DOI: 10.1021/bi901929n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for the Superior Activity of the Large Isoform of Snow Flea Antifreeze Protein

Abstract: The snow flea (Hypogastrum harveyi) is protected from freezing at sub-zero temperatures by a glycine-rich antifreeze protein (AFP) that binds to seed ice crystals and prevents them from growing larger. This AFP is hyperactive and comprises two isoforms [Graham, L. A., and Davies, P. L. (2005) Science 310, 461]. The larger isoform (15.7 kDa) exhibits several-fold higher activity than the smaller isoform (6.5 kDa), although it is considerably less abundant. To establish the molecular basis for this difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…MpAFP_RIV tagged with GFP for fluorescence-based ice plane affinity (FIPA) analysis (27) turned single ice-crystal hemispheres uniformly fluorescent (Fig. 5 B and C), consistent with the protein's affinity toward the basal and primary prism planes of ice, as well as surfaces between these planes, a property also seen with the hyperactive AFP from snow fleas (28). For a comparison, FIPA analysis was also performed on type I AFP.…”
Section: Resultsmentioning
confidence: 67%
“…MpAFP_RIV tagged with GFP for fluorescence-based ice plane affinity (FIPA) analysis (27) turned single ice-crystal hemispheres uniformly fluorescent (Fig. 5 B and C), consistent with the protein's affinity toward the basal and primary prism planes of ice, as well as surfaces between these planes, a property also seen with the hyperactive AFP from snow fleas (28). For a comparison, FIPA analysis was also performed on type I AFP.…”
Section: Resultsmentioning
confidence: 67%
“…Ice growth occurs from six prism surfaces and not out of the basal plane. However, when hyperactive AFPs are tested, most of them, including TmAFP, sfAFP (47), and MpAFP (7), bind to multiple planes as shown by adsorption to all surfaces of a single crystal hemisphere. GFP-tagged RiAFP also uniformly binds the entire surface of a single crystal hemisphere during fluorescence-based ice plane affinity analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The primary sequence of the large isoform of sfAFP is different from the primary structure of the small sfAFP isoform. Mok et al (2010) reported that the large isoform consists of 203 residues with a high occurrence of glycine. As in the small isoform, a tripeptide repeat pattern is observed in which glycine occupies the first position and often also the second.…”
Section: Controlling the Freezing Process With Antifreeze Proteinsmentioning
confidence: 99%